All work and all play: How McIntyre Library became our campus' playful experiential learning center - Hans Kishel; Helena Sumbulla; Liliana LaValle (University of Huddersfield Press, 2022)
While playing at work may sound incongruent, many of the staff at McIntyre Library at the University of Wisconsin - Eau Claire seek to provide the space and opportunities for students, staff, and faculty to infuse play into any aspect of their lives. To do this, we recognize a tension between being intentional with our outcomes, spaces, and programming, while providing flexibility for our users to improvise and discover what best serves their needs. After all, play is the clash of opportunity and creativity. Intrinsic to our work as librarians is a responsibility to our users; in encouraging play, both intentionally and unintentionally, our library invites users to assert themselves in a collaborative imagining of the tools, spaces, and resources we provide. By fostering an environment of playfulness, our staff strive to model and help users build skills for fun, lifelong experiential learning. In this article, we will trace McIntyre's trajectory of play over the years to its current iteration. We have refined our approach to play to be included in staff and professional development seminars, to encourage a holistic view of wellness in how spaces in the library are structured, to creating a Makerspace and Digital Studio lab, and to be included in outreach events in the hopes of making the library more accessible to students.